Some peculiarities of imprisonment as a preventive measure in criminal proceedings - Rogatynska, Nina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article discusses important issues preventive measure of detention in criminal proceedings. An application of the grounds of detention. Particular attention is giveto the petition prosecutor on the use of detention fed investigating judge.